Combined treatment with epoxyeicosatrienoic acid analog and 20-hydroxyeicosatetraenoic acid antagonist provides substantial hypotensive effect in spontaneously hypertensive rats - Gawrys, Olga; Husková, Zuzana; Baranowska, Iwona; Walkowska, Agnieszka; Sadowski, Janusz; Kikerlová, Soňa; Vaňourková, Zdeňka; Honetschlägerová, Zuzana; Škaroupková, Petra; Červenka, Luděk; Falck, John R; Imig, John D; et al. (Journal of hypertension, 2020)
OBJECTIVES: The global morbidity and mortality related to hypertension and associated disorders increases continuously and novel therapeutic strategies are still in high demand. Increasing evidence suggests the important role in blood pressure regulation of cytochrome P-450-dependent metabolites of arachidonic acid. Epoxyeicosatrienoic acids (EETs) induce vasodilation and natriuresis, and have renoprotective and anti-inflammatory properties. 20-HETE is an arachidonic acid metabolite with both prohypertensive and antihypertensive activities. To explore the pathophysiological role of arachidonic acid metabolites in more detail, we examined the antihypertensive efficiency of EET-A, a stable analog of 14,15-EET, and of AAA, a novel antagonist of the 20-HETE receptors. METHODS: Male spontaneously hypertensive rats (SHR) were treated for 5 weeks with EET-A, AAA or the combination; age-matched untreated SHR and normotensive Wistar-Kyoto rats served as controls. EET-A and AAA were administered in drinking water at 10 mg/kg/day each. SBP was measured by telemetry and urine, blood, and tissue samples were collected for relevant analyses. RESULTS: EET-A or AAA given alone had no significant effect on SHR blood pressure. In contrast, combined treatment with AAA and EET-A was significantly antihypertensive, causing a decrease in SBP from 180 ± 3 to 160 ± 5 mmHg (P < 0.05). Additionally, the combined treatment attenuated cardiac hypertrophy, decreased kidney ANG II level, increased natriuresis, and increased the excretion of nitric oxide metabolites. CONCLUSION: Considering the beneficial impact of the combined treatment with EET-A and AAA on SHR blood pressure and cardiovascular and renal function, we suggest that the treatment is a promising therapeutic strategy for human hypertension.
Keywords: Antihypertensive Agents; Blood Pressure; Rats, Inbred SHR; krysa rodu Rattus; potkani inbrední SHR; Male; antihypertenziva; hypertenze; Animals; Rats; kyseliny hydroxyeikosatetraenové; krevní tlak; mužské pohlaví; Eicosanoids; Hypertension; zvířata; ikosanoidy; Hydroxyeicosatetraenoic Acids